The Influence Of Psychological Hardiness, Narcissism, And Perfectionism On Depression Tendency Among Undergraduate Students - Akanbi, Samuel Toyin; Terwase, Joyce Mcivir; Aki, Benita Dooshima (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The aim of this study was to examine the role of psychological hardiness, narcissism, and perfectionism in depression tendency among undergraduate students in Oyo State, Nigeria. A quantitative research design using a correlational approach was adopted for the study. A total of 1,086 participants were selected through stratified random sampling. Four measuring instruments were used to garner data: Depression Proneness Rating Scale-11 (α=0.77), Dispositional Resilience Scale (α=0.73), Almost Perfect Scale-Revised (α=0.87), and Pathological Narcissism Inventory (α=0.91). Data were analyzed using Pearson’s product moment and multiple regression analysis. Findings revealed that predictors accounted for 42% of the total variance in depression tendency (R2=0.417; F(5, 1080)= 154.768; p<0.01). Each predictor indicated a significant relationship with the criterion (p<0.01). The study outcomes showed the need to consider variables analyzed in the present study while diagnosing depression symptoms among undergraduate students.